Puspamara Sendirian Berhad prospect and strategy / Nor Azman Zulkifli - Zulkifli, Nor Azman (1991)
Puspamara Sendirian Berhad is a Bumiputra company which operated in Petaling Jaya. The company manufactures textile products especially apparels and garments. Currently, the company main activity is supplying uniforms to the government agencies like the Armed Forces, Police and Customs. Puspamara also produces jackets for the purpose of exporting to the foreign market.